DEVELOPMENT OF AGRICULTURAL AND LIVESTOCK PRODUCT SALES SYSTEM FOR HOUSEWIVES IN KLAMBIR VILLAGE V KEBUN - Zulfahmi Syahputra; Hendry Hendry; Ristra Sandra Ritonga (INFOKUM, 2022)
During the COVID-19 pandemic, the number of businesses decreased in terms of sales so that some businesses went bankrupt. The Housewives' Group in Klambir Village V Kebun has a business that sells agricultural and livestock products. However, buyers are still limited to knowing the products of these businesses. In providing information about the business of the housewife group in Klambir V Kebun Village. For that we need a method of presenting information on the distribution of small industries that is better and can display various small industries accompanied by information on sales of agricultural and livestock products. Geographic Information System (GIS) can solve this problem by displaying the location of small industries in Medan along with information related to displaying more attractive products that can be accessed by the public. The Geographic Information System (GIS) will display in web form, so that it can be easily accessed by the public in ordering chips via the internet.